Aplicación del método de liofilización para la conservación de la base de cazuela manabita en la ciudad de Ambato provincia de Tungurahua. - Arévalo Cobeña, Ángel David (2025)
This research project was oriented in the study of food conservation by the method of freeze-drying in an Ecuadorian gastronomic preparation called casserole, an elaboration that requires a lot of care since it is exposed to particular transformation conditions due to its ingredients and the cultural food transcendence, strengthening the nutritional and composition knowledge of each of the elements that make it up emphatically taking the banana, the study takes an environmental analysis to the application of a survey with important information which allows the feasibility of the proposed with the transition of Its elaboration going through a clean manufacturing process showing possible causes of error that prevent obtaining an adequate freeze-drying, without generating causes of harmlessness of the product, the method of freeze-drying in the casserole generates a means of conservation without attacking the nutritional and organoleptic factors due to its freezing of fast method applied in a freezing abatement, sublimation reducing to 1.5 the atmosphere for its water dripping, its drying by means of temperature and time controls achieving an acceptable product for its initiation.